Rad GTPase Deletion Increases L‐type Calcium Channel Current Leading to Increased Cardiac Contraction. Issue 6 (12th December 2013) - Manning, Janet R.; Yin, Guo; Kaminski, Catherine N.; Magyar, Janos; Feng, Han‐Zhong; Penn, John; Sievert, Gail; Thompson, Katherine; Jin, J.‐P.; Andres, Douglas A.; Satin, Jonathan
Abstract : Background: The small GTPase Rad is a negative regulator of voltage‐dependent L‐type calcium channel current (IC aL ); however, the effects of Rad ablation on cardiomyocyte function are unknown. The objective of this study is to test the hypothesis that Rad‐depletion causes positive inotropic effects without inducing cardiac hypertrophy. Methods and Results: Ventricular myocytes from adult Rad −/− mice were isolated and evaluated by patch‐clamp recordings for ICa, L and action potentials, Ca 2+ transients, and sarcomere shortening. Maximum ICaL is elevated in Rad −/− (maximal conductance 0.35±0.04 picoSiemens/picoFarad (pS/pF) wild‐type; 0.61±0.14 pS/pF Rad −/− ), decay kinetics are faster, and ICa, L activates at lower voltages (activation midpoint −7.2±0.6 wild‐type; −11.7±0.9 Rad −/− ) mimicking effects of β‐adrenergic receptor stimulation. Diastolic and twitch calcium are elevated in Rad −/− ( F 340/380 : 1.03 diastolic and 0.35 twitch for wild‐type; 1.47 diastolic and 0.736 twitch for Rad −/− ) and sarcomere shortening is enhanced (4.31% wild‐type; 14.13% Rad −/− ) at lower pacing frequencies. Consequentially, frequency‐dependence of Ca 2+ transients is less in Rad −/−, and the frequency dependence of relaxation is also blunted. In isolated working hearts, similar results were obtained; chiefly, +dP/dt was elevated at baseline and developed pressure was relatively nonresponsive to acute β‐adrenergic receptor stimulation. In single cells, at subphysiological frequencies, nonstimulated calmodulin‐dependent protein kinase–sensitive calcium release is observed. Remarkably, Rad −/− hearts did not show hypertrophic growth despite elevated levels of diastolic calcium. Conclusions: This study demonstrates that the depletion of Rad GTPase is equivalent to sympathomimetic β‐adrenergic receptor, without stimulating cardiac hypertrophy. Thus, targeting Rad GTPase is a novel potential therapeutic target for Ca 2+ ‐homeostasis–driven positive inotropic support of the heart.